Isolation, biochemical characterization and phylogeny of a cellulose-degrading ruminal bacterium - Lorena Luna (Universidad de Antioquia, 2019)
Background: The isolation of cellulolytic bacteria, which hydrolyze cellulose to cellobiose and glucose, can provide useful information about rumen diversity. Objective: To identify and characterize a microorganism capable of hydrolyzing cellulose, isolated from a cow rumen. Methods: Anaerobic culture techniques were used for isolating cellulose-degrading rumen bacteria. Congo red staining was used to evaluate β-D-glucanase activity, and carbohydrate fermentation pattern was obtained with the kit API 50CHB/E. DNA extraction was performed and the 16S rDNA gene was amplified using 8F (5'-AGA GTT TGA TCC TGG CTC AG-3'), and 1492R (5' GGT TAC CTT GTT ACG ACT T 3') primers. The phylogenetic tree was reconstructed with the algorithm of maximum parsimony (bootstrap 5000), and 16S rDNA sequence was deposited in the NCBI database (accession number: KM094184). Results: The isolated bacterium showed cellulolytic activity detected with Congo red; besides, glycerol, ribose, xylose, sucrose, galactose and glucose were fermented by this bacterium. However, biochemical tests did not identify the bacteria because no match was found at database of API WEB Software. The phylogenetic inference indicated that this bacterium belongs to Shigella genus, with 98% maximal identity respect to the other taxonomic species. Conclusions: Phylogenetic analysis of 16S rRNA genes showed that the rumen isolated bacterium was a member of the genus Shigella, which, under mesophilic conditions, is an interesting candidate for obtaining oligosaccharides from lignocellulosic biomass.